(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Solid acid catalysts are environmentally friendly catalysts for a number of organic reactions (Wilson and Clark 2000) and those came into existence to avoid the use of conventional mineral acids that cause serious damage to the environment. The use of heterogenisation of catalysts and reagents as a method for achieving clean synthesis can lead to considerable reductions in wate produced in organic chemical manufacturing processes. Moreover, solid catalysts are potential in the manufacture of important fine chemicals through liquid phase transformations (Clark and Macquarrie 1997). Owing to the increasingly strict environmental system, researchers have paid more attention to solid acid catalysts to search for stable and eco-friendly catalysts. Multifunctional solids often are catalytically active, e.g. zeolites, alumina and certain forms of graphitic carbon.